PENGEMBANGAN MEDIA ROBALMEONCA (ROLLING BALL AND QUESTION CARD) PADA PEMBELAJARAN PENDIDIKAN PANCASILA KELAS IV SEKOLAH DASAR - Pertiwi, Bunga Arum Bella; Lian, Bukman; Aryaningrum, Kiki (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2025)
This study aims to develop a valid and practical media, specifically a rolling ball and question card, for the subject of Pancasila Education in the fourth grade of elementary school. The research type used is Research & Development (R&D) with the ADDIE model, which consists of five stages: analysis, design, development, implementation, and evaluation. The subjects of this study were the fourth-grade students at SD Negeri 34 Palembang. The validity test results showed an average of 83.52% from subject matter experts, 87.64% from language experts, and 91.26% from media experts, all falling under the "very valid" category. The practicality test results showed an average of 91.00% from a small group trial and 90.30% from teacher feedback, both categorized as "very practical." Therefore, it can be concluded that the rolling ball and question card media for Pancasila Education in the fourth grade at SD Negeri 34 Palembang is valid and practical.